Molecular characterization and nutritional regulation of specificity protein 1 (Sp1) in grass carp (Ctenopharyngodon idella). (20th October 2017) - Qu, F.; Tang, J.; Hu, R.; Hao, G.; Zhou, Y.; Lu, S.; Zhao, Q.; You, C.; Li, Y.; Zhou, Z.; Liu, Z.
Abstract: Specificity protein 1 (Sp1) is a ubiquitous nuclear factor in eukaryotic cells and plays a crucial role in the regulation of di‐/tripeptide absorption in the intestine. However, the function of Sp1 in bony fish remains poorly understood. In this study, a fish Sp1 gene (designated Ci Sp1) was identified from Ctenopharyngodon idella . The deduced Ci Sp1 protein contains structural features typical of Sp1 family proteins, including a glutamine‐rich (Q‐rich) region and three typical Cys2His2 zinc fingers. Quantitative real‐time PCR analysis revealed ubiquitous expression of Ci Sp1 in all tested tissues and embryonic developmental stages of grass carp. In addition, Ci Sp1 expression in the intestine was significantly increased after feeding with fish meal and 270 g/kg dietary protein. Moreover, in vitro and in vivo glutamine dipeptide treatments showed similar stimulatory effects on the expression of the transcription factors Ci Sp1 and Ci CDX2 and their potential target gene Ci PepT1 in the intestines of grass carp. Finally, our results demonstrated that the mRNA expression of Ci Sp1/ Ci CDX2/ Ci PepT1 in the intestine was significantly increased after treatment with sodium butyrate in vitro and in vivo. Altogether, these results demonstrate for the first time that grass carp possesses a functional Sp1 and that its expression is regulated by dietary protein and feed additives.